Analisis Perspektif Mahasiswa Pada Penerapan Kertas Kerja ATLAS (Audit Tool And Linked Archive System) - Sumanto, Agus; Rosdiana, Mega (BALANCE: Economic, Business, Management and Accounting Journal, 2023)
ABSTRACTIn the era of digitalization, auditors must keep up with the times. The "Financial Profession Development Center (P2PK)" has released the Microsoft Excel-based "ATLAS (Audit Tools and File Link System)" application. The purpose of the research was to find student perspectives on implementing the ATLAS application in the digital era. Later, this web-based application is expected to help "Certified Public Accountants (CPA)" and "Public Accountant Offices (KAP)" meet the audit requirements criteria. The application of these professional standards is documented in audit working papers supervised by the Ministry of Finance as documents reviewed by "P2PK (Center for Monitoring and Development of Finance)". As the "ATLAS (Audit Tools and Link Filing System)" application continues to grow, users of all levels, from accounting students taking audit internship courses to junior auditors, and senior auditors, from auditing frameworks to CPA partners, should use it. The discussion of this study is intended to assess the perceptions of UWKS accounting students regarding the "audit and implementation of the linked record system (ATLAS)" tool. This study uses a descriptive-quantitative approach, using a Likert scale to measure student perceptions. Based on the results of statistical tests, we found that there were differences of opinion among students about whether or not it was necessary to apply the ATLAS application in the learning audit practice course at Wijaya Kusuma University, Surabaya. In this sense, manual worksheets are no longer used because the ATLAS application must be applied at the time of the exam.ABSTRAK Di masa digitalisasi, auditor harus mengikuti arusperkembangan zaman. â€œPusat Pembinaan Profesi Keuangan (P2PK)â€ telah merilis aplikasi â€œATLAS (Audit Tools and File Link System)â€ berbasis Microsoft Excel. Tujuan penelitian yang dilakukan adalah untuk mengetahui perspektif mahasiswa terhadap implementasi aplikasi ATLAS di era digital. Nantinya, aplikasi berbasis web ini diharapkan dapat membantu â€œCertified Public Accountants (CPA)â€ dan â€œKantor Akuntan Publik (KAP)â€memenuhi kriteria persyaratan audit. Penerapan standar profesi tersebut didokumentasikan dalam kertas kerja audit yang diawasi oleh Kementerian Keuangan sebagai dokumen yang ditelaah oleh â€œP2PK (Pusat Pemantauan dan Pengembangan Keuangan)â€. Karena aplikasi â€œATLAS (Audit Tools and Link Filing System)â€ terus berkembang, pengguna di semua tingkatan, mulai dari mahasiswa akuntansi yang mengambil kursus magang audit, auditor junior, auditor senior, dari kerangka kerja audit hingga mitra CPA harus menggunakannya. Pembahasan studi ini ditujukan untuk dapatmenilai persepsi mahasiswa akuntansi UWKS mengenai alat â€œaudit dan implementasi linked record system (ATLAS)â€. Penelitian ini menggunakan pendekatan deskriptif-kuantitatif, dengan menggunakan skala Likert untuk mengukur persepsi mahasiswa. Berdasarkan hasil uji statistik, kami menemukan bahwa ada perbedaan pendapat di antara para mahasiswa tentang perlu atau tidaknya penerapan aplikasi ATLAS dalam mata kuliah praktik audit pembelajaran di Universitas Wijaya Kusuma, Surabaya. Dalam pengertian ini, kertas kerja manual tidak lagi digunakan, karena aplikasi ATLAS harus diterapkan pada saat ujian